Формирование коммуникативной компетентности будущих врачей на занятиях английского языка в медицинском университете - Жаворонкова, В. В.; Zhavoronkova, V. V.; Жаворонкова, Вікторія Василівна (Минск : БГУ, 2021)
В статье актуализированы вопросы формирования коммуникативной компетентности студентов медицинских университетов. Определены перспективы изучения и внедрения инновационных технологий обучения в процесс формирования коммуникативной компетентности будущих врачей в условиях медицинских университетов. The article presents the issues of forming the communicative competence of medical students. The prospects for the study and implementation of innovative teaching technologies in the process of forming the communicative competence of future doctors in the conditions of medical universities have been determined.
Formation of communicative competence of future doctors in english classes at a medical university
Keywords: английский язык; компетентность; коммуникативная компетентность; медицинский университет; формирование; English; competence; communicative competence; medical university; formation